Successful Management of Traumatic-Reticulo-Pericarditis in a Holstein Friesian Cow - Venkatesh, Atmakur; Mohanambal, Kaliyannan; Sumathi, Devaraju; Ravi, Ramasamy; Rakkiraja, Arasu; Elavarasan, Manivel; Karuppusamy Ponnu Swamy , Kallipatti (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Pericarditis refers to inflammation of the pericardium, often accompanied by the accumulation of serous or fibrinous inflammatory substances. In cattle, it is almost exclusively caused by a foreign object from the reticulum penetrating the reticular wall, diaphragm, and pericardial sac. Key signs of pericarditis include tachycardia, muffled heart sounds, abnormal and asynchronous heart sounds, distended jugular veins, and edema in the submandibular region, brisket, and ventral abdomen Braun, 2009. Ultrasonography is the preferred method for diagnosing and characterizing pericardial effusion. Echogenic deposits and fibrin strands are visible on the epicardium, and the ventricles appear compressed by the effusion. Severe pleural effusion is typically observed as well. In cattle presenting with jugular vein distension and tachycardia, this diagnostic approach is particularly valuable (Mohanambal et al., 2018). In this present case, pericardiocentesis along with conservative treatment helped for the successful recovery of the animal.
Keywords: accumulation; reticulum penetrating; Ultrasonography; Echogenic; tachycardia